Public Sector Transformation in the Digital Age: Obstacles and Challenges for the Government of Indonesia - Putri Hening; Gozali Harda Kumara (Iapa Proceedings Conference, 2019)
The world has now entered the digital era. Rapid technological developments spur the transformation from the manual era to the digital era. A series of trends in this era are present such as high-level usage of the internet, the birth of social networks, the development of various applications, and fast amount of information dissemination. This trend has brought a series of changes to various sector including the public sector. The presence of digital tools in this era has changed the way Indonesian government in providing public services. This era has also changed the community's approach to interact with the government through online platforms. The transformation into the digital era also influences the process of drafting public policies, from the agenda settings, policy formulation, implementation, until evaluation. Privacy and data security issues are also present in this era. This paper analyzes how the digital era has transformed the public sector in Indonesia and the obstacles and challenges faced by the Indonesian government. This paper will also provide recommendations to overcome these obstacles and challenges. This research is conducted by using qualitative and quantitative method. In analyzing data, researcher do three simultaneously activities based on Miles and Huberman model.